2018
DOI: 10.31436/imjm.v17i2.948
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a new Multidimensional Questionnaire called Muslim Medical Student Questionnaire (MMSQ) among Malaysian Undergraduates

Abstract: Introduction: A handful of medical schools have implemented the Islamic input in medical program into their medical curricula. However we are facing a setback as there is no validated standard assessment tool to measure the effectiveness of this academic input for undergraduate medical programme. Therefore the objective of this study is to design a scale that is able to gauge the impact of the Islamic input among medical undergraduates. Materials and Methods: The construction of a new scale is based on the 5 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Only the Knowledge subscale had a Cronbach's alpha value lower than 0.6 (0.59); however, this score was much better than that of the original version, which was only 0.13. 2 This result implied that the BI version of the MMSQ was appropriate for use in the Indonesian context.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Only the Knowledge subscale had a Cronbach's alpha value lower than 0.6 (0.59); however, this score was much better than that of the original version, which was only 0.13. 2 This result implied that the BI version of the MMSQ was appropriate for use in the Indonesian context.…”
Section: Discussionmentioning
confidence: 98%
“…The developer indicated that this item receives greater emphasis in the memorizing of the Qur'an rather than in the practice of reciting it. 2,11 Items P10 and P21 suggested that revision or rewording were required to improve their quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, items in Practice have better factor loadings (0.37-0.79) as compared items in Attitude and Knowledge domains. 10 The scale is named as the Muslim Medical Student Questionnaire (MMSQ). Drafting the scale was based on the Malaysian National Education Blueprint based on 3 important domains of Cognitive (knowledge), Affective (professionalism and personal development) and Psychomotor (skill).…”
Section: Measurement Tool; Muslim Medical Student Questionnaire (Mmsq)mentioning
confidence: 99%